BUSINESS PHILOSOPHY OF SELECTED BICOLANO ENTREPRENEURS: DISSECTING THEIR VIEWS AND INSIGHTS - Yumi Vivien De Luna (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aimed to seek views from selected Bicolano entrepreneurs on how they run their business, the values they believed, challenges they experienced with the current pandemic and their future plans as well. It was qualitative research that made used of structured interview and content analysis. Findings showed that Bicolano entrepreneurs’ views on the different themes were not clearly separated from each other. Most of them started the business as additional source of income. These entrepreneurs were strongly driven by their particular advocacies. In terms of core values, most of them agreed that dedication to work was viable in making business successful. The business philosophy that stood out among them was making customer satisfaction a priority. The resilience of the Bicolano entrepreneur amidst the pandemic was manifested by their continuous marketing innovations adapting to the situation.